Cartography of industrial heritage: Transformation and future of dismissed industries in the eastern zone of Lisbon - Pomesano, L.; Falanga, R. (Architecture, Structures and Construction, 2025)
This study examines the transformation of disused industrial heritage in the eastern area of Lisbon, specifically within the districts of Marvila and Beato, focusing on the dynamics of urban regeneration following deindustrialisation. The research highlights how, in a context characterised—similarly to other Southern European countries—by late-stage deindustrialisation, the industrial legacy of these areas has predominantly been repurposed to accommodate activities associated with the creative and cultural sectors. Using a tripartite methodology comprising a literature review, Geographic Information System (GIS) mapping, and industrial heritage characterisation through direct observation, alongside engagement with the ROCK (Regeneration and Optimisation of Cultural Heritage in Creative and Knowledge Cities) project, the study identified and characterised twelve former factories. Of these, nine have primarily been converted for artistic and cultural use, while two remain abandoned, emphasising the lack of significant public intervention. The article addresses the risks of gentrification and the increasing privatisation of industrial sites, raising concerns about preserving the identity and collective memory of these spaces. It underscores the need for integrated policies to ensure the protection and sustainable management of these sites. The article concludes with reflections on future prospects for safeguarding industrial heritage in urban contexts.